Encounters with Destiny : Autobiographical Reflections : A Translation of "Apna Garebaan Chaak" - Javid Iqbal, 1924-2015; Translated by Hafeez Malik and Nasira Iqbal (Lahore Sang-e-Meel Publications, 2012)
Autobiography of retired judge of the Supreme Court of Pakistan
Include Illustration
Keywords: Iqbal, Javid, 1924-2015 -- Pakistan -- Pakistan. Supreme Court